(untitled) (Colombia Medica, 2020)
Throughout the COVID-19 pandemic, the main risk factors associated with the progression to severe disease or death have been typically advanced age, diabetes mellitus, obesity, high blood pressure, heart disease, and chronic pneumopathy. Because of their immunosuppression status, persons with HIV were also expected to have a higher susceptibility to infection or a poor clinical evolution. So far, this has not been confirmed to happen, giving way to hypotheses about the role of immunosuppression or the use of antiretrovirals, which could explain this paradox. In this article we present the existing data on the epidemiology and characteristics of HIV-COVID-19 co-infection, discuss the available evidence on the possible factors involved in the evolution of individuals affected by both viruses, analyze other determinants that may negatively affect persons with HIV during the pandemic, and present recommendations for the prevention and care of COVID-19 infection in the context of HIV.